Comparison of the microstructural, physicochemical and sensorial properties of buffalo meat patties produced using bowl cutter, universal mixer and meat mixer - Ismail, Mohamad Afifi; Chong, Gun Hean; Ismail-Fitry, Mohammad Rashedi (Springer, 2021)
This work aimed to evaluate the microstructural, physicochemical and sensorial properties of buffalo meat patties produced using different mixing equipment (bowl cutter, universal mixer, and meat mixer). Scanning electron microscopy revealed a more homogenize emulsion, cohesive structure and smaller pore size of patties produced using the bowl cutter, which significantly reduced the total fluid release, water release, fat release and cooking loss as compared to the universal mixer and meat mixer. Production of the buffalo meat patties using bowl cutter also improved the moisture retention and gel strength of the patties. The patties produced using bowl cutter had the significantly highest lightness and yellowness values, while the redness was the lowest. Lower hardness, gumminess and chewiness also were observed from the patties produced using bowl cutter. Quality of the microstructural and physicochemical properties of the patties produced using different equipment can be organized as bowl cutter > universal mixer > meat mixer. Nevertheless, the sensory evaluation demonstrated a higher preference on aroma, flavour and overall acceptability of patties produced using meat mixer due to coarser and meaty texture, while the colour, tenderness, juiciness and springiness did not differ against using bowl cutter and universal mixer.